2018
DOI: 10.1016/j.bbi.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum to “Mind-body interactions in the regulation of airway inflammation in asthma: A PET study of acute and chronic stress” [Brain Behav. Immun. 58 (2016) 18–30]

Abstract: The authors regret that in this article, there was an error in the processing of the PET data for four participants, such that the order of the challenge conditions (stress or control) was incorrectly specified. As a consequence, the PET data were reprocessed. In reprocessing the data the general pipeline remained the same but FSL-and ANTS-based tools were used rather than SPM12. Only results pertaining to the PET data are affected by this error. The results from the corrected analysis are more straightforward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“… 8–10 In asthma, a highly prevalent chronic inflammatory disease characterized by reversible airway hyper-responsiveness, 11 a growing body of evidence indicates bidirectional lung-brain communication. 12–17 Several epidemiological studies have found that asthma increases the risk of cognitive impairment and dementia 18–20 suggesting that the lung-brain axis might be involved. There are, however, some studies that have found mixed or no evidence of the deleterious impact of asthma on brain health, 21–23 which highlights multiple challenges in determining the contribution of a particular inflammatory condition to dementia risk, such as the presence of other co-morbid conditions that might accentuate risk 7 or the potential protective effect of anti-inflammatory medications.…”
Section: Introductionmentioning
confidence: 99%
“… 8–10 In asthma, a highly prevalent chronic inflammatory disease characterized by reversible airway hyper-responsiveness, 11 a growing body of evidence indicates bidirectional lung-brain communication. 12–17 Several epidemiological studies have found that asthma increases the risk of cognitive impairment and dementia 18–20 suggesting that the lung-brain axis might be involved. There are, however, some studies that have found mixed or no evidence of the deleterious impact of asthma on brain health, 21–23 which highlights multiple challenges in determining the contribution of a particular inflammatory condition to dementia risk, such as the presence of other co-morbid conditions that might accentuate risk 7 or the potential protective effect of anti-inflammatory medications.…”
Section: Introductionmentioning
confidence: 99%